Responses in growth, lipid accumulation, and fatty acid composition of four oleaginous microalgae to different nitrogen sources and concentrations - 李涛 万凌琳 李爱芬 张成武 (Chinese journal of oceanology and limnology, 2013)
Nitrogen deficiency is an effective strategy for enhancing lipid production in microalgae. Close relationships exist among lipid production, microalgal species, and nitrogen sources. We report growth, lipid accumulation, and fatty acid composition in four microalgae （Chloroeoccum ellipsoideum UTEX972, Chlorococcum nivale LB2225, Chlorococcum tatrense UTEX2227, and Scenedesmus deserticola JNU19） under nitrate- and urea-nitrogen deficiencies. We found three patterns of response to nitrogen deficiency： Type-A （decrease in biomass and increase in lipid content）, Type-B （reduction in both biomass and lipid content）, and Type-C （enhancement of both biomass and lipid content）. Type-C microalgae are potential candidates for large-scale oil production. Chlorococcum ellipsoideum, for example, exhibited a neutral lipid production of up to 239.6 mg/（L＇d） under urea-nitrogen deficiency. In addition, nitrogen deficiency showed only a slight influence on lipid fractions and fatty acid composition. Our study provides useful information for further screening hyper-lipid microalgal strains for biofuel production.